2019
DOI: 10.1080/21645515.2019.1646577
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing influenza vaccine coverage among adults with high-risk chronic diseases in Spain from 2014 to 2017

Abstract: The objectives of this study were to estimate coverage of influenza vaccination in Spain among adults suffering chronic conditions, to assess time trends from 2014 to 2017 and to identify vaccine uptake predictors. We used individualized data of persons ≥15 y interviewed in the 2017 Spanish National Health Survey. Vaccine uptake and the presence of the chronic conditions analyzed (diabetes; cancer; chronic respiratory disease; chronic heart disease and cerebrovascular disease) were self-reported. Independent v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
5
21
0
Order By: Relevance
“…What these findings all show, however, is that further evidence is needed. Martínez et al [37] found that foreigners were less likely to uptake the vaccine than Spanish people, in line with the results of the present study. Some prior studies have reported similar findings regarding social and racial disparities on vaccination [53][54][55].…”
Section: Discussionsupporting
confidence: 92%
“…What these findings all show, however, is that further evidence is needed. Martínez et al [37] found that foreigners were less likely to uptake the vaccine than Spanish people, in line with the results of the present study. Some prior studies have reported similar findings regarding social and racial disparities on vaccination [53][54][55].…”
Section: Discussionsupporting
confidence: 92%
“…Oncologists should pay more attention to recommending vaccinations, because neoplastic diseases and related treatments can increase the patient’s susceptibility to infectious diseases with higher risk of hospitalization and mortality than the general population [ 34 , 35 ]. Adherence to influenza vaccination in this survey was similar to that observed in Spain among subjects with high-risk chronic conditions [ 23 ]. In the US, 37%, 39%, and 41% of patients with diabetes were immunized against pneumococcal disease, hepatitis B, and influenza, respectively [ 26 ] and 35.7% and 29.1% of adults aged ≥18 years with chronic liver disease reported having received ≥1 dose and ≥3 doses of hepatitis B vaccine, respectively [ 24 ], whereas in this sample only one in five with chronic hepatitis had been immunized against hepatitis B.…”
Section: Discussionsupporting
confidence: 78%
“…Patients with psychiatric problems or who were unable to respond to interview were excluded. The sample size was calculated assuming an expected proportion of vaccinated patients with chronic diseases for each recommended vaccine of 30% [ 23 , 24 , 25 ], a confidence interval (CI) of 95%, and an error rate of 5%. A 20% non-response rate was calculated and added, which increased the estimated sample size to 405.…”
Section: Methodsmentioning
confidence: 99%
“…Though influenza vaccination has been recommended by the WHO and other global organizations, annual influenza vaccine coverage remains to be relatively low in vulnerable populations. The overall influenza vaccination uptake rate among subjects with highrisk chronic conditions in Spain in 2017 was only 40.1% and decreased significantly from 2014 [41]. Though the rate among American children aged from 6 months to 17 years old increased from 16.70% during 2004/2005 to 49.43% during 2015/2016, it was still far below the U.S.…”
Section: Discussionmentioning
confidence: 97%